PENGARUH GLOBAL TERHADAP HUKUM LINGKUNGAN DI INDONESIA - Yanuarsi, Susi (Faculty of Law, University of Palembang, 2019)
The global environmental problem is a reflection of the international community on the occurrence of environmental damage and pollution that has engulfed the world due to development. Problems can be formulated on how the global impact of international environmental law conventions on environmental law in Indonesia. International conferences in the global environmental field will certainly have an effect on Indonesian legal politics in the environmental field. Government policies ratified various international conventions related to environmental protection. The environmental protection and management policy provides the concept of sustainable environmental development. Existing environmental legal instruments should be consistently enforced especially in the enforcement of environmental law. The importance of awareness of all components of the nation to develop the Indonesian state by relying on sustainable environmental development.